Preparation and Evaluation of GAC-Based Iron-Containing Adsorbents for Arsenic Removal - Gu, Zhimang; Fang, Jun; Deng, Baolin (Environmental science & technology, 2005)
Granular activated carbon-based, iron-containing adsorbents (As-GAC) were developed for effective removal of arsenic from drinking water. Granular activated carbon (GAC) was used primarily as a supporting medium for ferric iron that was impregnated by ferrous chloride (FeCl2) treatment, followed by chemical oxidation. Sodium hypochlorite (NaClO) was the most effective oxidant, and carbons produced from steam activation of lignite were most suitable for iron impregnation and arsenic removal. Two As-GAC materials prepared by FeCl2 treatment (0.025− 0.40 M) of Dacro 20 × 50 and Dacro 20 × 40LI resulted in a maximum impregnated iron of 7.89% for Dacro 20 × 50 and 7.65% for Dacro 20 × 40LI. Nitrogen adsorption−desorption analyses showed the BET specific surface area, total pore volume, porosity, and average mesoporous diameter all decreased with iron impregnation, indicating that some micropores were blocked. SEM studies with associated EDS indicated that the distribution of iron in the adsorbents was mainly on the edge of As-GAC in the low iron content (∼1% Fe) sample but extended to the center at the higher iron content (∼6% Fe). When the iron content was > ∼7%, an iron ring formed at the edge of the GAC particles. No difference in X-ray diffraction patterns was observed between untreated GAC and the one with 4.12% iron, suggesting that the impregnated iron was predominantly in amorphous form. As-GAC could remove arsenic most efficiently when the iron content was approximately 6%; further increases of iron decreased arsenic adsorption. The removal of arsenate occurred in a wide range of pH as examined from 4.4 to 11, but efficiency was decreased when pH was higher than 9.0. The presence of phosphate and silicate could significantly decrease arsenate removal at pH > 8.5, while the effects of sulfate, chloride, and fluoride were minimal. Column studies showed that both As(V) and As(III) could be removed to below 10 μg/L within 6000 empty bed volume when the groundwater containing approximately 50 μg/L of arsenic was treated.